Effect of temperature on the escape of charged polymer chain from a repulsive nanopore. Issue 13 (2nd September 2019) - Luo, Meng-Bo; Wu, Fan; Zhang, Shuang; Sun, Li-Zhen
ABSTRACT: The effect of temperature on the escape of a charged polymer chain from a repulsive nanopore is studied by Langevin dynamics simulations. The conformation properties of the charged polymer chain are dependent on the temperature as it is in random coil state at high temperature and in compact globule state at low temperature. The scaling behaviour between the escape time and polymer length is independent of temperature, while the escape time decreases with increasing the temperature in an exponential way. Different temperature-dependent behaviours are observed for the escape time in three temperature regimes: low temperature where the polymer is in compact globule state, intermediate temperature around the coil-to-globule transition temperature, and high temperature where the polymer is in the random coil state. We further find that, with a decrease in the temperature, the total number of moving steps for the escape increases sharply in the low-temperature regime while the time duration for each moving step increases sharply in the intermediate temperature regime.